PSXIII-7 Statistics and Tendencies for Dog Adoptions in the State of Washington. - Frosolone, A (J Anim Sci, 2018)
Shelters often experience overcrowding, understaffing, lack of resources and economic issues that are reflected in animal stress and poor welfare. The aim of the present study was to analyze statistical tendencies to determine the length of stay (LOS) of dogs in shelters in Washington state between 2010–2017. Data on 7407 dogs from five shelters were included in the analysis. The average LOS was 21.7 days, ranging from 0–1834.0 days. Statistical differences were observed among shelters (Pwas statistically different regarding LOS (P (juveniles 15 years: 59.4 days). Breed also affected LOS (PAccording to intake type (reason why they enter the shelter), LOS was statistically different (P<0.001) (surrendered: 33.5 days, seized: 30.9 days, clinic: 0.17 days, stray: 9.9 days, transferred: 13.9 days, and unknown: 60.3 days). Likewise, outcome type (reason why the leave the shelter) was statistically different (P<0.001) (adopted: 33.5 days, clinic-out: 2.1 days, died: 27.7 days, euthanized: 2.9 days, transferred: 15.3 days, returned to owner: 6.9 days, fostered: 184.0 days and unknown outcome: 33.5 days). Finally, a significant interaction between breed, age and intake type (P<0.0001) and breed, age and outcome type (P<0.0001) was observed. In conclusion, some characteristics inherent to the dog such as breed and age influence the intake and outcome of the permanence at the shelter, therefore future strategies to target adoptions based on these characteristics will decrease the duration of stay and maximize shelter resources ultimately improving animal welfare.